Cellulose nanocrystals induce a dose-dependent effect on cytotoxicity and proliferative activity of human peripheral blood mononuclear cells - Miloš Vasiljević; Sergej Tomić; Marina Bekić; Bojan Joksimović; Dragana Vučević; Miodrag Čolić (Биомедицинска истраживања, 2020)
Introduction: Cellulose nanocrystals (CNCs) as attractive natural materials, have numerous applications in the biomedical field. Their unique biomechanical characteristics, surface chemistry, low cost and sustainable nature make them an engaging alternative to conventional materials and potentiate their use as progressive material. Therefore, it is critical to evaluate the cytocompatibility and immunomodulatory properties of nCNCs, which have not been completely explored. The objective of this study was to examine a dose-dependent effect of native (n)CNCs on cytotoxicity and proliferative activity of human peripheral blood mononuclear cells (PBMNCs) in vitro. Methods: PBMNCs, obtained from the healthy blood donors, were cultivated with nCNCs. Cell viability was analyzed by flow cytometry assay, while proliferative activity was determined by MTT, [3H]-thymidine uptake assay and detection of IL-2 production. Results: The cytotoxicity results suggested that no concentration of nCNCs (50-400 mg/ml) affected necrosis of PBMNCs, whereas apoptosis was induced by the highest concentration of nCNCs compared to control (p<0.05). Unexpectedly, the highest concentration of nCNCs increased the metabolic activity of PHA-stimulated cells compared to control (p<0.05). In contrast to these findings, lower concentrations of nCNCs (50 mg/ml and 100 mg/ml) stimulated proliferation of PBMNCs (p<0.05 and p<0.001). It was followed by increased production of IL-2 (100 mg/ml) (p<0.001). Conclusion: The results suggest that non-cytotoxic concentrations of nCNCs modulate the proliferative activity of human PBMNCs, a phenomenon which has not been published up to now and which is relevant for further studies.
Keywords: cellulose nanocrystals; peripheral blood mononuclear cells; culture; cytotoxicity; proliferative activity